Law and social change in postwar Japan - Upham, Frank K. (Harvard University Press, 1987)
This book is about law and social change in contemporary Japan. It examines the way in which elites use legal rules and institutions to manage and direct conflict and control change at a social level. Given the common view of Japan as having little conflict and less law, this topic will strike some as unusual. In most accounts of postwar Japan, social life is portrayed as virtually conflict-free, the result of a society where the Confucian ideals of social harmony and antipathy toward law have been internalized by a loyal and cooperative population.